Inhibitory effect of aromatic herbs, lavender, sage and chamomile against herpes simplex virus infection - Raenu Yucharoen (2018)
This study demonstrated anti-herpes simplex virus (HSV) activity of lavender, sage and chamomile extracts. Green monkey kidney cells were protected from HSV-2 infection by dichloromethane and methanol extract of lavender with therapeutic indices (TI) of 1.98 and 2.90, respectively when the cells were treated before viral infection. Moreover, the dichloromethane extract of chamomile showed the highest TI which was 20.74 against HSV-1 when the virus was treated during adsorption. The inhibitory effect of dichloromethane extract of lavender significantly had the highest TI (45.90) when HSV-1 was treated after viral adsorption. The highest inhibitory effect against HSV-2 was observed after treatment of the virus with methanol and dichloromethane extracts of sage, with TIs of 9.02 and 10.1, respectively. Chamomile extracts showed significant virucidal effects on both HSV-1 and HSV-2 viral particles. The inhibitory effect of chamomile extracts on HSV-1 and HSV-2 viral yield after viral replication was the highest at 30 h after treatment. Respective reductions of viral titers by 9.7 and 7.1 fold were observed when cells were treated with dichloromethane and methanol extract of chamomile. Therefore, chamomile, sage and lavender were demonstrated to possess anti-herpes simplex virus activities at various stages of the viral multiplication cycle. © 2011 Academic Journals.